Silage additive update: 1985 - K.K. Bolsen; J.D. Hoover (Kansas Agricultural Experiment Station Research Reports, 1985)
Silage additives are receiving fairly widespread acceptance in the U.S. as management tools that are important for silage-making. Many products, which are added to the crop at the time of harvest or ensiling, are available commercially in Kansas. Some manufacturers/distributors make no claims for their products, primarily because management is such an important factor in making a good quality silage. Others claim their product will improve silage quality. When a claim is made, it is wise to check for evidence that the product has a favorable effect on the silage crop in question. Farm-scale silo trials at Kansas State University have shown that a few silage additives repeatedly reduced "in silo" losses. But results will probably not be favorable with all additives under every farm condition. Therefore, results obtained with a commercial product in our trials may not apply to other products on the market, however similar in ingredient formulation.; Dairy Day, 1985, Kansas State University, Manhattan, KS, 1985;
Keywords: Kansas Agricultural Experiment Station contribution; no. 86-94-S; Report of progress (Kansas Agricultural Experiment Station); 484; Dairy; Silage; Quality; Maturity; Moisture